2021
DOI: 10.1002/mco2.100
|View full text |Cite
|
Sign up to set email alerts
|

Tumor metastasis: Mechanistic insights and therapeutic interventions

Abstract: Cancer metastasis is responsible for the vast majority of cancer‐related deaths worldwide. In contrast to numerous discoveries that reveal the detailed mechanisms leading to the formation of the primary tumor, the biological underpinnings of the metastatic disease remain poorly understood. Cancer metastasis is a complex process in which cancer cells escape from the primary tumor, settle, and grow at other parts of the body. Epithelial‐mesenchymal transition and anoikis resistance of tumor cells are the main fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 410 publications
(501 reference statements)
2
42
0
Order By: Relevance
“…Metastasis is considered as one of the primary reasons leading to a worse survival rate in breast cancer patients [ 51 , 52 ]. The lung and liver are generally accepted as the primary target sites of breast cancer metastasis [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Metastasis is considered as one of the primary reasons leading to a worse survival rate in breast cancer patients [ 51 , 52 ]. The lung and liver are generally accepted as the primary target sites of breast cancer metastasis [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given WNT7B is typically involved in canonical WNT signaling, we then investigate whether this invasion capability was attributed to canonical signaling downstream genes. According to the probable WNT target genes ( http://web.stanford.edu/group/nusselab/cgi-bin/WNT/target_genes ), we chose CDH1 (cadherin1) and matrix metalloproteinases (MMPs) as candidates because they show a high correlation with tumor invasion and metastasis [ 21 , 22 ]. We compared the mRNA abundance of all WNT downstream MMP members and CDH1 in normal, OLP, and cancer tissues using our previous data (GSE70666) [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tumor invasion and metastasis are challenges in the clinical treatment of HCC. EMT is regarded as a critical step in tumor invasion and metastasis [36]. A previous study suggested that CHRNA5 could regulate the migration and invasion ability of melanoma cells [23].…”
Section: Discussionmentioning
confidence: 99%